The validity of O'Sullivan's classification system (CS) for a sub-group of NS-CLBP with motor control impairment (MCI): Overview of a series of studies and review of the literature - Dankaerts, W.; O'Sullivan, Peter (Elsevier, 2011)
Chronic Low Back Pain (LBP) remains a common, recalcitrant and costly problem for the individual sufferer and for society. Effective treatments that reduce the social and economic burden have yet to be established for the majority of chronic LBP cases. Lack of evidence for specific interventions has been blamed on the heterogeneity of the chronic LBP population as well as a lack of a patient centred biopsycho-social approach. This issue of heterogeneity has resulted in classification being considered the highest research priority in the area of chronic LBP. The potential for a ‘wash-out effect’ caused by the heterogeneity of the chronic LBP populations sampled for randomised controlled clinical trials (RCTs), has driven the need for classifying patients with nonspecific chronic LBP. A summary of a series of studies is outlined in this review paper. They represent a comprehensive investigation into the validity of O’Sullivan’s proposed mechanism-based classification system (CS) for a sub-group of localized mechanically provoked nonspecific chronic LBP with motor control impairment (MCI). Further, the findings of these studies are discussed in relation to the relevant literature and the clinical implications arising are presented. Finally, the limitations of this research are outlined and recommendations for future research are made.